Arc/Arg3.1 function in long‐term synaptic plasticity: Emerging mechanisms and unresolved issues. (10th October 2020) - Zhang, Hongyu; Bramham, Clive R.
Abstract: Arc (activity‐regulated cytoskeleton‐associated protein) is posited as a critical regulator of long‐term synaptic plasticity at excitatory synapses, including long‐term potentiation, long‐term depression, inverse synaptic tagging and homoeostatic scaling, with pivotal roles in memory and postnatal cortical development. However, the mechanisms underlying the bidirectional regulation of synaptic strength are poorly understood. Here we review evidence from different plasticity paradigms, highlight outstanding issues and discuss stimulus‐specific mechanisms that dictate Arc function. We propose a model in which Arc bidirectionally controls synaptic strength by coordinate regulation of AMPA‐type glutamate receptor (AMPAR) trafficking and actin cytoskeletal dynamics in dendritic spines. Key to this model, Arc is proposed to function as an activity‐dependent regulator of AMPAR lateral membrane diffusion and trapping at synapses. Abstract : Arc is multifunctional in synaptic plasticity. We discuss stimulus‐specific mechanisms that dictate Arc function and propose a model in which Arc bidirectionally controls synaptic strength by coordinate regulation of AMPA‐type glutamate receptor (AMPAR) trafficking and actin cytoskeletal dynamics in dendritic spines. Key to this model, Arc is proposed to function as an activity‐dependent regulator of AMPAR lateral membrane diffusion and trapping at synapses.